EFFECT OF GENETIC MAKEUP AND SEASON ON FERTILITY AND HATCHABILITY OF CHICKEN VARIETIES OF RURAL FARMING - D. Gandhimathi; M. Murugan; S.C. Edwin (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data of 229 hatches of commercial country chicken hatchery for a period of four years from 2017-2020 was collected and analyzed to study the effect of genetic makeup and season on fertility and hatchability in chicken varieties developed for rural chicken rearing viz., Aseel cross, Kaveri, Grampriya and Vanaraja. Kaveri chicken varieties recorded significantly higher fertility of 85.04 per cent (P